The GnRH antagonist acyline prevented ovulation, but did not affect ovarian follicular development or gestational corpora lutea in the domestic cat - Risso, Analia Lorena (2010)
Two experiments were conducted to investigate the effects of the GnRH antagonist acyline (330 microg/kg, given sc) on ovarian follicular development and ovulation, as well as on pregnancy maintenance in domestic cats. In the first experiment, seven queens in proestrus (total of 24 proestrus periods), were randomly assigned to treatment with either acyline (ACY; n=17) or a placebo (PLC; n=7). All queens were mated with a fertile tomcat. In the ACY and PLC groups, cessation of estrus occurred (mean+/-SEM) 7.0+/-1.3 and 7.0+/-1.7 d after treatment (P>0.1), ovulation occurred in 2 of 17 and all seven estrus periods (P<0.05), and pregnancy rates were 1 of 16 and 7 of 7 (P<0.05), respectively. In the ACY and PLC groups, intervals from treatment to the onset of the ensuing proestrus were 18.4+/-1.7 and 120+/-17.2 d. In the second experiment, 14 pregnant queens were randomly allocated, according to their mating date, to treatment with acyline in early pregnancy (from 20 to 25 d, n=3), mid pregnancy (from 26 to 45 d; n=4), late pregnancy (> 45 d; n=3), or injection of a placebo in early (n=1), mid (n=2), or late pregnancy (n=1). Ultrasonographic assessments of the uterus were done every second day for 2 wk post treatment, and serum progesterone (P(4)) concentrations were determined before treatment, and at 7 and 14 d after treatment. No pregnancies were prematurely terminated and post-treatment P(4) concentrations did not differ among treatment groups (P>0.1). In conclusion, in the domestic cat, GnRH withdrawal by acyline prevented ovulation when given in early follicular phase (proestrus), but did not significantly affect luteal function during pregnancy.